2012
DOI: 10.1080/09291016.2011.599638
|View full text |Cite
|
Sign up to set email alerts
|

Morning-to-evening difference of biomarkers of muscle injury and antioxidant status in young trained soccer players

Abstract: The aim of this study was (i) to evaluate whether homocysteine (Hcy), total antioxidant status (TAS), and biological markers of muscle injury would be affected by time-of-day (TOD) in well-trained soccer players. In a counterbalanced order, 20 soccer players participated on two different occasions between 07:00 and 08:30 h and between 17:00 and 18:30 h. Fasting blood samples were collected from a forearm vein during each session. The results showed that the values of white blood cells (WBC), neutrophils (NE), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 32 publications
6
23
0
2
Order By: Relevance
“…These fi ndings are in agreement with previous studies that have identifi ed peak times for these variables to be situated between 18:00 and 24:00 h in healthy sedentary subjects [ 14 , 19 ] . We recently found similar results in trained subjects [ 11 ] . After the Wingate test, the present hematological results showed increases of RBC, HCT and WBC (as well as their subpopulations) at both times of testing.…”
Section: Hematology Resultssupporting
confidence: 73%
“…These fi ndings are in agreement with previous studies that have identifi ed peak times for these variables to be situated between 18:00 and 24:00 h in healthy sedentary subjects [ 14 , 19 ] . We recently found similar results in trained subjects [ 11 ] . After the Wingate test, the present hematological results showed increases of RBC, HCT and WBC (as well as their subpopulations) at both times of testing.…”
Section: Hematology Resultssupporting
confidence: 73%
“…It is well established that athletic performances display a diurnal pattern with higher values measured in the late afternoon and lower measures observed in the early morning (12). Likewise, it has been shown that soccer players perform at an optimum between 16:00 h and 20:00 h when soccerspecific skills and measures of physical performance are at their peak (18).…”
Section: Discussionmentioning
confidence: 99%
“…MEL, often considered as a chronobiotic (12), was initially investigated in terms of its role in endocrine physiology regulating circadian and sometimes seasonal rhythms (22). Moreover, it has been shown that exogenous MEL can improve sleep quality and alleviate jet lag symptoms after transmeridian travels (5).…”
mentioning
confidence: 99%
“…As with the inflammatory biomarkers, measured biomarkers of oxidative stress are affected by the above discussed lifestyle changes that accompany Ramadan (89)(90)(91)(92)(93)(94)(95)(96), and the relationship with the timing of the blood samples to mealtime (90). Previously discussed studies collected only a single early morning blood sample.…”
Section: Effects On Oxidative Stressmentioning
confidence: 99%
“…Previously discussed studies collected only a single early morning blood sample. Oxidant levels could have been affected by the sample collection time as well as by the interaction between sample collection time and mealtime (91,93). The blood sample collection time of oxidant or anti-oxidant activity may affect the measured levels.…”
Section: Effects On Oxidative Stressmentioning
confidence: 99%